Cache Aware Optimization of Stream Programs - Sermulins, Janis; Thies, Bill; Rabbah, Rodric; Amarasinghe, Saman (Conference on Languages, Compilers, and Tools for Embedded Systems (LCTES 2005). Chicago, IL, 2005)
Effective use of the memory hierarchy is critical for achieving high performance on embedded systems. We focus on the class of streaming applications, which is increasingly prevalent in the embedded domain. We exploit the widespread parallelism and regular communication patterns in stream programs to formulate a set of cache aware optimizations that automatically improve instruction and data locality. Our work is in the context of the Synchronous Dataflow model, in which a program is described as a graph of independent actors that communicate over channels. The communication rates between actors are known at compile time, allowing the compiler to statically model the caching behavior. We present three cache aware optimizations: 1) execution scaling, which judiciously repeats actor executions to improve instruction locality, 2) cache aware fusion, which combines adjacent actors while respecting instruction cache constraints, and 3) scalar replacement, which converts certain data buffers into a sequence of scalar variables that can be register allocated. The optimizations are founded upon a simple and intuitive model that quantifies the temporal locality for a sequence of actor executions. Our implementation of cache aware optimizations in the StreamIt compiler yields a 249% average speedup (over unoptimized code) for our streaming benchmark suite on a StrongARM 1110 processor. The optimizations also yield a 154% speedup on a Pentium 3 and a 152% speedup on an Itanium 2.